TAX INCENTIVES FOR COMPANIES TO INVEST: THE PORTUGUESE CASE IN 2019 - Amorim, Jose Campos; Sousa, Benjamim; Pereira, Adalmiro; Vaz, Angela (PEOPLE: International Journal of Social Sciences, 2020)
The allocation of tax incentives aims to stimulate the economy by reducing or exempting, directly or indirectly, taxes, thus allowing the reduction of the tax burden, but also attracting new investments in the key sectors of the economy, can be a way to develop a country. The recently approved Investment Tax Code in Portugal creates new rules for obtaining tax benefits, which it is important to know here and is the main object of study here. The results show that companies benefiting from this cab obtain considerable tax savings and tax efficiency. It is important to clarify the several options that the companied can have and what is the best solution. So, a review of the most important options is extreme relevant. This paper presents a group of examples that demonstrate the ways the companies can benefit with the incentives presents in the Portuguese law.